2010
DOI: 10.1021/nn101973p
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Manipulation of Strong Coupling in Metal−Molecular Aggregate Hybrid Nanostructures

Abstract: We demonstrate an ultrafast manipulation of the Rabi splitting energy Ω(R) in a metal-molecular aggregate hybrid nanostructure. Femtosecond excitation drastically alters the optical properties of a model system formed by coating a gold nanoslit array with a thin J-aggregated dye layer. Controlled and reversible transient switching from strong (Ω(R) ≃ 55 meV) to weak (Ω(R) ≈ 0) coupling on a sub-ps time scale is directly evidenced by mapping the nonequilibrium dispersion relations of the coupled excitations. Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
217
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 175 publications
(226 citation statements)
references
References 38 publications
8
217
1
Order By: Relevance
“…The primary method of probing the dynamics of many photo-physical systems is that of pump-probe spectroscopy (see for example [156]). Vasa et al used pump-probe spectroscopy to investigate samples comprising J-aggregate layers deposited onto gold gratings [150]. They first showed that strong coupling was present in such systems, an anti-crossing appearing on their dispersion diagram, a diagram produced using experimentally determined reflectivity data, anti-crossing appearing where the grating-scattered SPP mode crossed the exciton absorption.…”
Section: Dynamics In J-aggregate Strong Couplingmentioning
confidence: 99%
“…The primary method of probing the dynamics of many photo-physical systems is that of pump-probe spectroscopy (see for example [156]). Vasa et al used pump-probe spectroscopy to investigate samples comprising J-aggregate layers deposited onto gold gratings [150]. They first showed that strong coupling was present in such systems, an anti-crossing appearing on their dispersion diagram, a diagram produced using experimentally determined reflectivity data, anti-crossing appearing where the grating-scattered SPP mode crossed the exciton absorption.…”
Section: Dynamics In J-aggregate Strong Couplingmentioning
confidence: 99%
“…Despite these clear and consistent observations, the relaxation dynamics of the polaritons into the noncoupled MEs, as well as scatterings among them, are still not fully understood. 25,31,32 Recent time-resolved studies have shed some light on the issue, 33,34 and have demonstrated Rabi oscillations as a clear signature of strong coupling. 35 However, at the same time there has been significant evidence about unexpectedly long lifetimes of the polaritons, 36 suggesting more pronounced scattering or maybe even thermalization among them.…”
Section: Introductionmentioning
confidence: 99%
“…1b. Spectra reveal significant bending of the SPP and exciton resonances due to the formation of the upper (UP) and lower (LP) SPP-exciton polaritons, [2,5] with normal mode splitting, Ω NMS~1 10 meV. This strong normal mode splitting reflects the coupling of J-aggregate excitons localized near the nanoslits to the locally enhanced evanescent near field of the SPP.…”
Section: Metal/molecular Hybrid Nanostructure and Its Linear Responsementioning
confidence: 99%
“…1a using sub-15 fs pulses, sufficient to temporally resolve coherent exciton-SPP wavepacket dynamics. Figure 2 shows representative data displaying differential reflectivity spectra To analyze these results and to uncover the underlying physics, we have performed extensive density matrix simulations of the coupled system considering the molecular aggregate as a three level system exhibiting an exciton-biexciton transition while the SPP mode is modeled as a photonlike oscillator [2,3]. Essentially, the following scenario emerges.…”
Section: Coherent Ultrafast Manipulation Of the Rabi Energymentioning
confidence: 99%
See 1 more Smart Citation